Energy transfer-induced tunable emission color and thermal quenching of Ca3Y(PO4)3: Eu2+, Mn2+ phosphor for NUV-pumped white LEDs. (August 2016) - Tian, Yue; Feng, Ningning; Wierzbicka-Wieczorek, Maria; Huang, Ping; Wang, Lei; Shi, Qiufeng; Cui, Cai'e
Abstract: A series of Eu 2+ doped and Eu 2+ /Mn 2+ co-doped Ca3 Y(PO4 )3 phosphors have been synthesized by high temperature solid-state route. In the Eu 2+ -doped samples, an intense and broad green emission band is presented under the excitation of 370 nm light. Emission color changing from green to warm white light is observed when different concentrations of Mn 2+ ions were introduced into the lattice of Ca3 Y(PO4 )3 :Eu phosphor, originating from an efficient energy transfer from Eu 2+ to Mn 2+ ions. The energy transfer mechanism from Eu 2+ to Mn 2+ is demonstrated to be a quadrupole–quadrupole interaction based on the concentration quenching as well as the energy transfer efficiency of 90%. The temperature-dependent luminescence of Ca3 Y(PO4 )3 :Eu 2+, Mn 2+ phosphor reveal that 52% of initial intensity can be kept at 150 °C, suggesting good thermal stability of the phosphor. Our results indicate that the Ca3 Y(PO4 )3 :Eu 2+, Mn 2+ phosphor may be a potential candidate for use as near ultraviolet pumped white light-emitting diodes phosphor. Graphical abstract: Highlights: Eu 2+ /Mn 2+ doped Ca3 Y(PO4 )3 phosphors were prepared for the first time. The fast cooling rate is crucial to obtain the pure-phased Ca3 Y(PO4 )3 phosphors. Warm white light is achieved via energy transfer from Eu 2+ to Mn 2+ ions. Eu 2+ /Mn 2+ co-doped Ca3 Y(PO4 )3 phosphor exhibits good thermal stability.